Effects of acidified aqueous glycerol and glycerol carbonate pretreatment of rice husk on the enzymatic digestibility, structural characteristics, and bioethanol production. (March 2017) - Ebrahimi, Majid; Villaflores, Oliver B.; Ordono, Emma E.; Caparanga, Alvin R.
Highlights: Glycerol carbonate solvent as a novel pretreatment was performed on rice husk. A small portion of acids as a catalyst mixed with the pretreatment solvents. AGC treatment improved glucan digestibility and lignin removal more than AAG treatment. Ethanol production of 11.58 and 8.84 g/L obtained from SSF under anaerobic condition. Abstract: Rice husk as an abundant biomass was used in this study, and it contained 30.1% glucan and 13.5% xylan, 22.4% lignin. The pretreated rice husk with glycerol carbonate and acidified aqueous glycerol (10% water) at 90 °C and 130 °C for 60 min had the maximum yield of glucan digestibility which was 78.2% and 69.7% respectively, using cellulase for 72 h. The simultaneous saccharification and fermentation was conducted anaerobically at 37 °C with Saccharomyces cerevisiae, 5% w/v glucan and 10 FPU/g glucan of cellulase. 11.58 and 8.84 g/L was the highest ethanol concentration after 3 days of incubation form pretreated rice husk with glycerol carbonate and acidified aqueous glycerol respectively.